Memory in Elementary School Children Is Improved by an Unrelated Novel Experience - Ballarini, F. (2013)
Education is the most traditional means with formative effect on the human mind, learning and memory being its fundamental support. For this reason, it is essential to find different strategies to improve the studentś performance. Based on previous work, we hypothesized that a novel experience could exert an enhancing effect on learning and memory within the school environment. Here we show that novel experience improved the memory of literary or graphical activities when it is close to these learning sessions. We found memory improvements in groups of students who had experienced a novel science lesson 1 hour before or after the reading of a story, but not when these events were 4 hours apart. Such promoting effect on long-term memory (LTM) was also reproduced with another type of novelty (a music lesson) and also after another type of learning task (a visual memory). Interestingly, when the lesson was familiar, it failed to enhance the memory of the other task. Our results show that educationally relevant novel events experienced during normal school hours can improve LTM for tasks/activities learned during regular school lessons. This effect is restricted to a critical time window around learning and is particularly dependent on the novel nature of the associated experience. These findings provide a tool that could be easily transferred to the classroom by the incorporation of educationally novel events in the school schedule as an extrinsic adjuvant of other information acquired some time before or after it. This approach could be a helpful tool for the consolidation of certain types of topics that generally demand a great effort from the children. © 2013 Ballarini et al.